TB-IRIS, T-cell activation, and remodeling of the T-cell compartment in highly immunosuppressed HIV-infected patients with TB. (28th January 2015) - Haridas, Viraga; Pean, Polidy; Jasenosky, Luke D.; Madec, Yoann; Laureillard, Didier; Sok, Thim; Sath, Sun; Borand, Laurence; Marcy, Olivier; Chan, Sarin; Tsitsikov, Erdyni; Delfraissy, Jean-François; et al.
<x xml:space="preserve">Abstract</x> Objective: To investigate the impact of tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) upon immunological recovery and the T-cell compartment after initiation of TB and antiretroviral therapy (ART). Design and methods: We prospectively evaluated T-cell immunophenotypes by flow cytometry and cytokines by Luminex assays in a subset (n = 154) of highly immunosuppressed HIV-infected patients with TB from the Cambodian Early versus Late Introduction of Antiretrovirals randomized clinical trial. We compared findings from patients who developed TB-IRIS with findings from patients who did not develop TB-IRIS. Data were evaluated with mixed-effect linear regression, Kaplan–Meier estimates, and Wilcoxon rank-sum tests, and q-values were calculated to control for multiple comparisons. Results: Development of TB-IRIS was associated with significantly greater pre-ART frequencies of HLA-DR+CD45RO+CD4+, CCR5+CD4+, OX40+CD4+, and Fas+ effector memory CD8+ T cells, and significantly elevated levels of plasma interleukin (IL)-6, IL-1β, IL-8, and IL-10, and viral load. Post-ART initiation, effector memory CD4+ and Fas+ effector memory CD4+ T-cell frequencies significantly expanded, and central memory CD4+ T-cell frequencies significantly contracted in patients who experienced TB-IRIS. By week 34 post-TB treatment initiation, effector memory/central memory CD4+ T-cell ratios were markedly higher in TB-IRIS versus non-TB-IRIS patients. Conclusions: A distinct pattern of pre-ART T-cell and cytokine markers appear to poise the immune response of certain patients to develop TB-IRIS. Experience of TB-IRIS is then associated with long-term remodeling of the CD4+ T-cell memory compartment towards an effector memory-dominated phenotype. We speculate that these pre and post-ART TB-IRIS-associated immune parameters may contribute to superior immune control of TB/HIV co-infection and better clinical outcome.